2017
DOI: 10.3390/rs9080840
|View full text |Cite
|
Sign up to set email alerts
|

Topic Modelling for Object-Based Unsupervised Classification of VHR Panchromatic Satellite Images Based on Multiscale Image Segmentation

Abstract: Abstract:Image segmentation is a key prerequisite for object-based classification. However, it is often difficult, or even impossible, to determine a unique optimal segmentation scale due to the fact that various geo-objects, and even an identical geo-object, present at multiple scales in very high resolution (VHR) satellite images. To address this problem, this paper presents a novel unsupervised object-based classification for VHR panchromatic satellite images using multiple segmentations via the latent Diri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…For multiresolution segmentation, numerous studies have demonstrated the importance of the scale parameter. The scale parameter controls the dimension and size of segmented objects, which may directly affect subsequent results [47][48][49]. In numerous applied studies, land-cover extraction mainly relied on a trial-and-error approach, with segmentation scale parameters determined based on previous experience [50].…”
Section: Multiresolution Segmentation Using Ts Imagesmentioning
confidence: 99%
“…For multiresolution segmentation, numerous studies have demonstrated the importance of the scale parameter. The scale parameter controls the dimension and size of segmented objects, which may directly affect subsequent results [47][48][49]. In numerous applied studies, land-cover extraction mainly relied on a trial-and-error approach, with segmentation scale parameters determined based on previous experience [50].…”
Section: Multiresolution Segmentation Using Ts Imagesmentioning
confidence: 99%
“…Alternatively, Geographic Object-Based Image Analysis can be used to delineate spatial regions by grouping adjacent pixels into homogeneous areas according to the objectives of the study [23,24]. For biodiversity research, image segmentation has been used to automatically derive homogeneous vegetation units based on spectral [25] or a combination of spectral and structural (height) information [16,26].…”
Section: Remote Sensing For Ecotope Mappingmentioning
confidence: 99%
“…We propose the Local Hierarchical Dirichlet Process (Local-HDP), an extension of the Hierarchical Dirichlet Process [11] method, which can incrementally learn new topics for each category of objects independently. In contrast to the notable recent works [8,12,13] using a predefined number of topics, Local-HDP is more flexible since it is a non-parametric Bayesian model that can autonomously determine the number of topics for each category at run-time. Figure 2 shows the processing layers of the proposed Local-HDP.…”
Section: Introductionmentioning
confidence: 99%